Analysis of the Isotopes Hydrogen Mixtures from Cryogenic Distillation Separation using Gas Chromatography - Preda, Anisoara; Pearsica, Claudia; Bornea, Anisia; Vasut, Felicia; Zamfirache, Marius (Asian Journal of Chemistry, 2010)
A gas chromatographic system for the analysis of gas species of hydrogen is very important for the separating of hydrogen species by cryogenic distillation, catalyst isotopic exchange and another processes. This paper will present the analysis of gas species of hydrogen samples which had been taken from the top and the bottom of the cryogenic distillation column at different pressures of the column.